Peculiarities of seasonal allergy in children in the South Ukrainian region - Kuznietsova, O. D.; Кузнєцова, Олена Дмитрівна (Киров: Кировская гос. мед. академия, изд-во ООО «Веси», 2015)
Allergy remains one of the principle and relevant problems in modern pediatrics. According to WHO data the prevalence of allergic diseases (in particular – allergic rhinitis) is highest in United Kingdom and Ukraine and is 40 per 1000. Climatic and geographic conditions, development of ag-riculture and industry in Zaporoahye region are favorable for seasonal allergy and leads to increasing in its prevalence and severity.
Keywords: тези